Características in vivo e de carcaça de ovinos e caprinos comercializados para abate no estado do Ceará - Albuquerque, Ítalo Araújo (2013)
It was evaluated the in vivo and carcass traits of sheep and goats sold for slaughter in the state of Ceará. A total of 48 animals, 24 sheep and 24 goats, male, non-castrated, were used. Initially, in a randomized experimental design, with 2x3 factorial with six replications, where two species and three origins, carcass and commercial cuts zoometrics characteristics were evaluated and compared. The animals, undefined breed (SRD), average age of 12 months, were purchased at open markets in the capital of the state, they were raised under extensive production system, coming from regions of higher effective and use of these species: Sertão Central, Região Norte and the Sertão dos Inhamuns, represented by the municipalities of Quixadá, Sobral and Tauá, respectively. Subsequently, in a randomized experimental design, with a 2x2 factorial with six replications, with two species and two production systems, the in vivo, carcass and commercial cuts characteristics of animals SRD, arising from a conventional extensive production system and animals raised in intensive production systems semi-intensive were evaluated and compared. These animals, Santa Inês crossbred sheep and Boer crossbred goats, weaned at 60 days of age with creep-feeding, raised on native pasture thinned with concentrate supplementation and an average age of six months, were purchased from a commercial breeding facility of sheep and goats in the city of Caridade - Ceará. After fasting of 24 h for solid diet and 16 h of liquid diet, all animals were weighed to obtain the live weight at slaughter (PVA), which was measured, also, the body condition of the animal and biometric measurements: body length (CC), height of the anterior (AA), height of the posterior (AP), chest width (LP1), rump width (LG1), chest perimeter (PT1) and compactness index body (ICC1 kg/cm). After the procedures for slaughter, the carcasses were weighed to obtain the hot carcass weight (PCQ) and, once cooled, re-weighed to obtain the cold carcass weight (CCW), and calculated the percentage loss by cooling (PPR). Then, it was determined the hot carcass yield (RCQ) and cold carcass yield (RCF). The carcasses were hung next to each other, and subjective evaluations for conformation and finishing were performed. Subsequently, the following measurements were performed on the carcasses: carcass external length (CEC), hindquarters width (LG2), hindquarters perimeter (PG), thorax width (LT), chest width (LP2), chest perimeter (PP), carcass internal length (CIC), leg length (CP), chest depth (PT2), and the determination of carcass compactness index (ICC2 - kg/cm) and leg (ICP1 - cm). After the neck removal, half carcass was divided into five anatomical parts denominated commercial cuts - leg, shoulder, ribeye, rib and sawcut. The pieces were weighed, and their respective yields were obtained based on the weight of the cold carcass recovered (PRC), and the compactness index of the leg (ICP2-kg/cm). It was obtained the maximum width (A) and maximum depth (B) of Longissimus lumborum, determining the ribeye area - AOL. The subcutaneous fat thickness (EGS) was also measured. Pearson correlations were performed between the in vivo measurements and the carcass and commercial cuts measurements of the animals. Comparing the origins and species reared in extensive system and commercialized for slaughter in open fairs in the capital, in relation to in vivo measurements, body weight (PVA) averaged was 23.83 ± 3.76 kg for goats and 25.22 ± 5.25 kg for sheep, with body condition score (EC) proximate to 2 and a mean age of 12 months, with no differences between species (P>0.05). For the housing of these animals, the hot (PCQ) and cold (PCF) carcass weight ranged between 9 and 10 kg, with no difference between species and origins (P>0.05) for carcass weights, yields and cooling loss. The conformations of the carcasses were evaluated as little fat cover to those very thin, and by the heterogeneity of values of goat carcasses, there was such superiority in relation to these aspects in relation to the sheep carcasses (P<0.05), and the sheep presented higher values (P<0.05) in ribeye area (AOL), subcutaneous fat thickness (EGS) and greater leg weight and proportion compared to the goats. Concluding, undefined breed goats and sheep, bred under extensive system in the state of Ceará and sold in open markets in the capital, regardless of origin region, reach slaughter weight with advanced age and lean body condition, resulting in inferior quality carcasses, poor muscle proportion and little fat covering. Regarding comparisons between species and production systems, it was observed superiority in almost all variables, for animals kept in semi-intensive production system compared to animals raised under extensive conventional system, more practiced in the state, and, still, presenting oldest animals. Thus, to obtain early goats and sheep, with better carcass and retail cuts weight and quality in the state of Ceará, providing, this way, a quality product to strengthen the sector production of goats and sheep, it is recommended to intensify the extensive system of production, using kids and lambs for slaughter, with improved genetics, health and nutrition of livestock.